Pengaruh Pandemi Covid-19 terhadap Pengunjung Objek Pariwisata Sejarah Lobang Jepang di Bukittinggi - Mellyana Alfia Ningsih; Isjoni Isjoni; Bedriati Ibrahim (LP4MK STKIP PGRI Lubuklinggau, 2022)
The Japanese hole is a protection tunnel built by the Japanese occupation army around 1942. Japanese hole or Japanese hole (Minang language designation) is a tourist attraction located in the West Sumatra area, precisely in the middle of a panoramic garden in Sianok Gorge under Bukittinggi City. This Japanese hole has a length of 1,470 meters and is winding. This tunnel is located about two meters below the ground level of the city of Bukittinggi. The Japanese hole in the city of Bukittinggi is the longest tunnel in Southeast Asia with 21 passageways with various functions. This Japanese hole is a long historical tunnel for the Indonesian people in general because this Japanese hole is a refuge or hiding place for Japanese soldiers in the face of war. The Japanese hole was built with the aim of defending the Japanese army in World War II and the Greater East Asia War. This study will discuss (1) the Effect of the Covid-19 Pandemic on Visitors of the Japanese Lobang Historical Tourism Object in Bukittinggi; (2) Management of Japanese Hole Historical Tourism Objects During the Covid-19 Pandemic; and (3) Preventive Measures taken by the Management of the Japanese Lobang Tourism Object during the Covid-19 Pandemic. In this study, researchers used quantitative methods. The data collection instrument used in this study was a questionnaire consisting of 29 statements. The population in this study are visitors who come to the historical tourist attraction of the Japanese hole. Sampling in this study used incidental sampling technique. The results showed that there was an influence between the covid-19 pandemic on visitors to the historical tourism object of the Japanese hole in Bukittinggi. This is evidenced by a simple linear regression analysis. It is known that the value of Fcount is greater than the value of Ftable (4.002 > 3.868), the value of tcount is greater than the value of ttable (2.001 > 1.966). In addition, the value of sig. 0.046 or less than 0.05. Thus, Ho is rejected and Ha is accepted. This means that the COVID-19 pandemic significantly affects visitors to the historical tourism object of the Japanese hole.